How deep is deep enough? Ocean iron fertilization and carbon sequestration in the Southern Ocean. Issue 7 (11th April 2014) - Robinson, J.; Popova, E. E.; Yool, A.; Srokosz, M.; Lampitt, R. S.; Blundell, J. R.
Abstract : Artificial ocean iron fertilization (OIF) enhances phytoplankton productivity and is being explored as a means of sequestering anthropogenic carbon within the deep ocean. To be considered successful, carbon should be exported from the surface ocean and isolated from the atmosphere for an extended period (e.g., the Intergovernmental Panel on Climate Change's standard 100 year time horizon). This study assesses the impact of deep circulation on carbon sequestered by OIF in the Southern Ocean, a high‐nutrient low‐chlorophyll region known to be iron stressed. A Lagrangian particle‐tracking approach is employed to analyze water mass trajectories over a 100 year simulation. By the end of the experiment, for a sequestration depth of 1000 m, 66% of the carbon had been reexposed to the atmosphere, taking an average of 37.8 years. Upwelling occurs predominately within the Antarctic Circumpolar Current due to Ekman suction and topography. These results emphasize that successful OIF is dependent on the physical circulation, as well as the biogeochemistry. Key Points: Carbon export to 1000 m does not guarantee sequestration in the Southern Ocean OIF requires consideration of the circulation as well as biogeochemistry Sequestered carbon is dispersed widely out of the Southern Ocean by circulation